Laurobasidium hachijoense, comb. nov.(Cryptobasidiaceae) causing aerialroot-like galls on Cinnamomum japonicum in Japan - Kakishima, Makoto; Nagao, Hideyuki; Denchev, Cvetomir M. (Magnolia Press, 2017)
A new combination, Laurobasidium hachijoense, is proposed to accommodate Exobasidium hachijoense from Japan, producing aerialroot-like galls on stems of Cinnamomum japonicum. This combination is based on the presence of a gastroid-like sporulation on the surface of the galls, and is supported also by the host-plant specialization and molecular data.A fungus producing aerialroot-like galls on the trunks and stems of Cinnamomum japonicum (Lauraceae) was found in 1984 and was described as a new species, Exobasidium hachijoense Y. Otani et al. (Iijima et al. 1985). This species is similar to E. lauri Geyl. on stems of Laurus azorica (Seub.) Franco and L. nobilis L. (Geyler 1874) in gall and sorus structures, but different in morphological features of basidia—the number of sterigmata per basidium and the size of basidium (Iijima et al.1985)